Indonesia assessment 1995 : development in Eastern Indonesia - Barlow, Colin; editor; Hardjono, Joan; editor; ISEAS (Singapore : ISEAS, 1996)
With the Research School of Pacific and Asian Studies, Australian National University
Keywords: Indonesia -- Economic conditions -- 1945.; Indonesia -- Economic policy; Indonesia -- Politics and government -- 1966.; Indonesia -- Social conditions; Rural development -- Indonesia